2021
DOI: 10.1007/s00436-021-07194-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel variant erythrocyte surface antigen-1 (VESA1) in Babesia orientalis

Abstract: Babesia orientalis , belonging to the phylum Apicomplexa, is mainly accountable for water buffalo babesiosis, which adversely affected the livestock industry in China. Variant erythrocyte surface antigen-1 (VESA1), an antigen that helps infected erythrocytes to escape from host immune responses, was first reported in Babesia bovis. Various VESA1 proteins have also been characterized in other Babesia species. Nevertheless, there is no research on the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Given the fact that ves2 exists in the homologous positions of smorf, it was suggested that ves2 is analogous to smorf in these parasites [66]; however, the function of both gene families is unknown. VESA1 from B. bovis was experimentally confirmed to be expressed on the iRBCs surface [28], and VESA1 from B. orientalis was shown to be exported to iRBC [68]. While in B. bovis VESA1 is responsible for cytoadhesion and antigenic variation [69], cytoadhesion has not been documented for other Babesia spp., despite the presence of expanded ves gene families in their genomes.…”
Section: Immune Evasion and Cytoadhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the fact that ves2 exists in the homologous positions of smorf, it was suggested that ves2 is analogous to smorf in these parasites [66]; however, the function of both gene families is unknown. VESA1 from B. bovis was experimentally confirmed to be expressed on the iRBCs surface [28], and VESA1 from B. orientalis was shown to be exported to iRBC [68]. While in B. bovis VESA1 is responsible for cytoadhesion and antigenic variation [69], cytoadhesion has not been documented for other Babesia spp., despite the presence of expanded ves gene families in their genomes.…”
Section: Immune Evasion and Cytoadhesionmentioning
confidence: 99%
“…bovis was experimentally confirmed to be expressed on the iRBCs surface [ 28 ], and VESA1 from B . orientalis was shown to be exported to iRBC [ 68 ]. While in B .…”
Section: Introductionmentioning
confidence: 99%